Implantable Cardioverter-Defibrillator - Cheraou, Salwa; Erraboun, Nahid; Hamami, Amine; Ibtissam, Fellat; Cherti, Mohamed (RA Journal Of Applied Research, 2020)
Introduction: Sudden cardiac death (SCD) is a public health problem with an incidence of 3 million worldwide. In most cases, it is secondary to heart rhythm disturbances of ventricular origin. The only treatment with proven efficacy is the implantation of an implantable cardioverter-defibrillator (ICD). Materials and methods: We report a retrospective and descriptive study comprising 13 patients implanted with an ICD in our department and collected between 2010 and 2019. Results: The average age of the patients is 44 years with a predominance of men. The distribution of etiologies shows a clear predominance of genetic heart disease. The symptomatology at implantation was mainly palpitations. 46% of patients in the series are implanted prophylactically. The single-chamber DAI is the most established (53.8%). Conclusion: Our study first confirmed that ICD saves lives. It is the standard treatment for ventricular rhythm disorders, both in primary and secondary prevention of sudden death. At the B cardiology department of the Rabat University Hospital, the general characteristics of the population studied are similar to those described in the literature with regard to the indications for implantation and patient follow-up are respected.